2016
DOI: 10.1007/s12640-016-9689-2
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside Increases Permeability of Osseous Spiral Laminae of Cochlea by Interrupting MMP-2 and MMP-9 Balance

Abstract: The spiral ganglion neurons (SGNs) located in the Rosenthal's canal of cochlea are essential target for cochlear implant. Previous studies found that the canaliculi perforantes, small pores on the surface of the osseous spiral lamina (OSL) of the scala tympanic (ST) of cochlea, may provide communication between the cochlear perilymph and SGNs. In this study, we found that chronic treatment of aminoglycosides antibiotics, which is well known to cause sensory cell damage in the cochlea, induced significant damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Expression of MMP2 in the cytosol of type I spiral ganglion neuron was consistent with imaging in the rat spiral ganglion [73,112]. We are also able to report expression of MMP2 in the outer spiral bundle.…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)supporting
confidence: 82%
See 2 more Smart Citations
“…Expression of MMP2 in the cytosol of type I spiral ganglion neuron was consistent with imaging in the rat spiral ganglion [73,112]. We are also able to report expression of MMP2 in the outer spiral bundle.…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)supporting
confidence: 82%
“…MMP2 is a matrix metalloproteinase that degrades type IV collagen, which may play a role in the elongation of neuronal outgrowths during development and extracellular matrix remodeling after tissue damage. Several experiments in guinea pig and rat models for cochlear damage have demonstrated that that Mmp2 RNA expression increases after noise exposure [71], ototoxic aminoglycoside antibiotics [73,112], and cochlear implantation [72]. Aminoglycosides also increased the permeability of the osseous spiral lamina in rat cochlea, which led to increased diffusion across canaliculi perforantes from the scala tympani and scala vestibuli to spiral ganglion neurons embedded in Rosenthal's canal [73].…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have con rmed that naturally existing tiny openings in the osseous spiral lamina (OSL) provide communication for dyes and neural growth factors to move between the scala tympani (ST) and the cochlear modiolus where sit the SGNs. Due to the small diameter of these openings (2-20 um), only a single cell can pass through (9). When transplanted to the ST, stem cells will congregate and are unable to pass through the pores as single cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that ≥50% of cases of congenital deafness have genetic causes. At present, the etiology of hearing loss remains largely unknown, although gene alterations (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and environmental factors, including aminoglycoside antibiotics (AmAn), are now generally considered to be involved in this condition (16).…”
Section: Introductionmentioning
confidence: 99%